7.4 Subtracting Linear Expressions
Distributing the Negative If there is a negative sign on the out side of the parenthesis add a 1 to it and distribute a -1. Examples: 1.) –(3x+2) = -1(3x+2) = -3x + (-2) 2.) – ( -x – 3) = -1 ( -x -3) = x +3 3.) - (-2x+1) =-1 (-2x+1) =2x -1 4.) – (3x -5) = -1(3x -5) = -3x +5 What do you notice about the signs? The negative on the outside switches the signs on the inside
Steps to Subtract Linear Expressions 1.Change the subtraction into addition of its inverse (KFC) 2.Put a 1 in front of the 2 nd () 3.Distribute the -1 to the 2 nd () 4.Add the two linear expressions together with whichever method you like
(7x-5)-(2x-1) (7x + -5) + -1 (2x + -1) (7x + -5 ) + (-2x +1)
(6x -4) – (2x-4) (6x + -4) + -1(2x +-4) (6x + -4) + (-2x + 4)
(x-5) – (2x-1) (x+ -5) + - 1(2x + -1) (x+ -5) + (-2x + 1)
(6m +3) – (-4m – 1) (6m+3) + -1(-4m + -1) (6m+3) + (4m +1)
The expression 9x +27 represents the total amount of money a band earned from selling x CDs. a.) If the band had to pay (3x+ 12) dollars in expenses, what is the expression that represents their profit (9x+27) – (3x+12) (9x +27) + -1(3x+12) (9x+27) + (-3x + -12) b.) If the band sold 125 CDs, what was their profit? 6x +15, x= 125 6(125) $765
Homework Page 312 (1-12) all